Peran Filsafat Pendidikan Islam dalam Mengembangkan Potensi Individu Masyarakat Berbasis Rohani - El-Yunusi, Muhammad Yusron Maulana; Safiani, Aulia Mufidatus; Mahbubah, Siti Mafridatul (TSAQOFAH, 2023)
Education is a learning process carried out to restore individual potential in order for them to in order for them to achieve their desired life goals within the context of Islamic education has a broader dimension, namely in addition to achieving life goals in the world, education also aims to attain happiness in their lives. The philosophy of Islamic education has an important role in developing spiritual-based individual and community potential. In a spiritual-based society, Islamic education plays a crucial role in molding the moral fabric of a community. with noble character and piety to Allah. Through Islamic education, people can understand basic values and principles in Islam and apply them in everyday life. Islamic educational philosophy also talks about the purpose of human life which includes spiritual, moral and intellectual aspects. Apart from that, philosophy also assists in formulating effective educational approaches and methods in obtaining a deeper and deeper understanding of Islamic teachings. honesty, fairness, and empathy.